Counter-Radicalization in Madrasah: Implementation The Values of Religious Moderation at Man Insan Cendekia Padang Pariaman West Sumatra - Wahyuni, Dwi (Proceedings of International Conference on Muslim Society and Thought, 2024)
Since 2019, the Indonesian government has launched a program to strengthen religious moderation as a strategic step to counter-radicalization in various sectors of public institutions. Among these important sectors are madrasas. However, how madrasah residents respond to the idea of religious moderation and what religious moderation is like in practice, still needs to be researched more comprehensively. This article aims to show the response and implementation of religious moderation at MAN Insan Cendekia Padang Pariaman. A qualitative research method was employed with a case study approach. Data were collected through in-depth interviews, observation and document analysis. This article shows that at MAN Insan Cendekia Padang Pariaman, there is critical acceptance of diverse moderation and its implementation occurs in intra-religious tolerance. The implementation of various moderation that has occurred at MAN Insan Cendekia Padang Pariaman shows the success of madrasas in counter-radicalization